Comparison of Weak Load Bus Detection using LQP_LT Index with PV and QV Analysis of PSS/E - Renuga Verayiah; Azah Mohamed (Institute of Advanced Engineering and Science, 2018)
Identification of weak load buses which contributes to voltage instability problem is crucial in order for an appropriate mitigation action to be executed. The current power system transmission is not only stressed to deliver high load demand at the receiving end but also facing new challenges brought by the penetratrion of renewable energy sources. This new scenario requires power system operation and analysis to be robust and fast in detecting the accurate weak load bus for correction action. Due to this, many online indices to detect weak load bus during power system contingency have been developed. Nevertheless, LQP_LT is of the latest index developed which ultimately has the reactive power tracing capability for weak load bus detection and generate priority ranking list of the weak load buses. This index was tested on IEEE 14 bus test system for different contingency scenarios. The results obtained from the LQP_LT index is compared and validated with the PV and QV analyses obtained using industrial graded PSS/E software. It was concluded that the LQP_LT index is found to be robust, efficient and need less computation time as compared to the execution of voltage stability analysis using the PSS/E Tool.